Are there any distributive effects of land title on labor supply? Evidence from Brazil - Mauricio Jose Serpa Barros de Moura; Marcos Ribeiro; Caio Piza (IZA Journal of Labor & Development, 2014)
This paper investigates the effects of land titling on labor supply for households heads. The effect of legal ownership security on the adult labor supply is identified by comparing the impact of being part of, or excluded from, a land title program in a unique public intervention in two neighboring communities in the Brazilian city of Osasco. We employ a quasi-experimental technique to identify the average treatment effect on treated by using diff-in-diff and ANCOVA methods. We also estimate distributive impact on the hours worked by adults by estimating unconditional quantile treatment effects. The results suggest that the impact of land titling on labor is positive and greater at the median of the "weekly hours worked" distribution.
Keywords: J18; J22; K11; R38; 330; Land titling; Labor supply; Average treatment effect; Quantile treatment effect